Dietary approaches reducing boar taint—Importance of Lawsonia intracellularis colonisation for interpreting results. (5th April 2018) - Visscher, C.; Kruse, A.; Sander, S.; Keller, C.; Mischok, J.; Tabeling, R.; Henne, H.; Deitmer, R.; Kamphues, J.
Summary: In the fattening of male pigs, boar odour is a major problem with regard to the acceptance of the meat by consumers. Skatole can be one cause. Tryptophan from non‐digested feed ingredients and intestinal cell debris can be the precursor in skatole formation. Lawsonia intracellularis, one of the most widespread pathogens in swine, promotes the epithelial cell turnover and might favour the tryptophan influx into the hindgut. Therefore, the question arises how far the severity of a Lawsonia intracellularis infection has an effect on results of dietary experiments with specific issues. Fifty finishing boars from a specific pathogen‐free farm were randomly allotted to ten boxes in five feeding groups. Natural developing Lawsonia intracellularis colonisation was monitored serologically (twice individually) and molecular biologically (weekly individually). Over 4 weeks, animals were fed either a finely ground pelleted diet (FP), a coarsely ground meal diet (CM), a meal diet either with 22% cracked corn (CORN), 16.9% dried whey (WHEY) or 30% raw potato starch (RPS). Fifty % of animals showing lower differences in serological Lawsonia intracellularis values between the start and the end of the trial were characterised by a higher dry matter content in faeces (256 ± 29.4 vs. 239 ± 23.6 g/kg). Lawsonia intracellularis‐ negative caecal samples showed the highest butyrate concentrations (27.2 ± 7.53 mmol/kg). Lawsonia intracellularis ‐negative faecal samples of group FP showed the highest DM levels in faeces (neg: 290 ± 46.1/pos: 250 ± 52.2 g/kg); negative samples from group RPS had the lowest values (217 ± 24.4 g/kg). Lawsonia intracellularis ‐negative faecal samples from the group CM were lower in skatole than positive samples (82.8 ± 32.8 vs. 119 ± 29.3 μg/g DM). RPS group samples without pathogen detection had the lowest skatole concentrations (30.5 ± 36.3 μg/g DM). This study provides first evidence that clinically unremarkable colonisation with intestinal pathogens might influence the results of dietary approaches.